DEWAN PENGAWAS SYARIAH DAN PROFESIONALISME SUMBER DAYA MANUSIA - Masse, H. Rahman Ambo (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Sharia Supervisory Board (DPS) is one of the most important part in the system of Islamic financial and banking institutions in Indonesia. The existence of DPS is recognized based on applicable laws and regulations. The existence of DPS in sharia financial institutions and sharia banking aims to oversee sharia principles that must be implemented in real terms in the contract system and transactions in Islamic financial and banking institutions. Empirically, the recognition of legislation on the existence of DPS has not been fully implemented by Islamic financial and banking institutions. In fact, recommendations regarding the findings of sharia principles violations in the contract system and transactions in sharia financial and banking institutions often receive a response from the board of directors. Therefore, the most important indicator that DPS must have is the professionalism of its human resources. Competence is a determinant factor in recruiting DPS. These competencies include aspects of mastery of fiqh muamalah theories, competency in reading financial statements, and competencies in the field of engagement law.